Le lien entre le paysage des cinq sens (gokan no fūkei 五感の風景) et la vie quotidienne du furusato - Tanaka Naoto (Projets de Paysage)
The aim of this article is to highlight aspects of the relationship certain local communities, such as villages or neighbourhoods, have with their landscapes and to identify existing regulations that should be built upon to make these relationships sustainable. The hypothesis put forward is that the relationship between people and the landscape is constructed in the form of a "ba" or a collective place. Processes for the construction of such places are therefore presented as guiding principles for reflection. These collective places or ba can take two forms : the collective place of autonomy (jichi no ba 自治の場) and the collective place of integration (tōgō no ba 統合の場). Two case studies focus on the need to change this relationship between a local community and its landscapes through the protection of the cultural landscapes of an agricultural plateau of medium altitude. The plateau in question is the Shiraito plateau on the island of Kyūshū where the relationship between the landscape and local communities was disrupted during the disastrous Kumamoto earthquakes in 2016.